Correlation between elevated bradykinin concentrations and death by COVID-19 - Fani, Mona; Ghasemzadeh-Moghaddam , Hamed; Belkum, Alex; Shoraka, Hamid Reza; Azimian , Amir; Hosseini , Zahra (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To investigate BK pathway dysregulation among and between COVID-19 survivors and the deceased. Methodology: This case-control study was performed between 2020 and 2022 in Imam Hasan Hospital, Bojnurd, Iran. SARS-CoV-2 infected patients, comprising 40 deceased and 15 surviving patients, were recruited according to specific inclusion and exclusion criteria. A blood sample was taken from subjects during the disease. Blood BK levels in subjects (the groups of patients (55) and control (15)) were measured by the ELISA technique. All patients were selected from individuals over 18 years old with real-time PCR-proven SARS-CoV-2 infection. Also, the studied patients did not have metabolic syndrome (blood pressure, abdominal obesity, diabetes, cardiovascular disease). SPSS version 26 was used to compare the means. Results: The blood serum BK level was significantly related to the outcome of COVID-19 disease (P=0.006) using a multiple logistic regression test. A week before death, a significant increase in the blood BK levels among deceased patients compared to survivors was seen (p=0.0001). The probability of death in patients with SARS-CoV-2 infection linearly increased by 4% (OR = 1.04) for each pg/ml increase in the BK level. Conclusion: There is a close relationship between the rise in BK concentration during a COVID-19 infection and the disease outcome.